2020
DOI: 10.1002/term.3114
|View full text |Cite
|
Sign up to set email alerts
|

The combination of a poly‐caprolactone/nano‐hydroxyapatite honeycomb scaffold and mesenchymal stem cells promotes bone regeneration in rat calvarial defects

Abstract: Bone tissue engineering goes beyond the limitations of conventional methods of treating bone loss, such as autograft-induced morbidity and a lack of integration for large grafts. Novel biomimicry approaches (using three-dimensional [3D] electrospinning and printing techniques) have been designed to offer the most appro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
(66 reference statements)
0
14
1
1
Order By: Relevance
“…But they have several limitations to restrict their widespread applications, such as limited supply, complications at donor sites, risks of disease transmissions, and so on [ 4 , 5 ]. Bone tissue engineering, including scaffolds, cells and growth factors, offers a promising approach to overcome these limitations and draws more attentions from researchers in recent years [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…But they have several limitations to restrict their widespread applications, such as limited supply, complications at donor sites, risks of disease transmissions, and so on [ 4 , 5 ]. Bone tissue engineering, including scaffolds, cells and growth factors, offers a promising approach to overcome these limitations and draws more attentions from researchers in recent years [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, hydroxyapatite microparticles were electrosprayed simultaneously with the electrospinning of PLA giving rise to biomimetic honeycomb‐like materials for bone regeneration promoting in vitro and in vivo osteoconduction, and osteoinduction. [ 16,17 ] Hierarchical fibrous carbon catalysts can also be envisaged with such a strategy. [ 46 ] The periodic deposition of catalytic active phases embedded in the electrosprayed particles allows the growth of carbon nanofibers (CNFs) by subsequent chemical vapor deposition in periodic areas of the carbon composite.…”
Section: Resultsmentioning
confidence: 99%
“…[8] However, one of the advantages of electrospinning over its competitors is its ability to guide the deposition of the nanofiber on micropatterned collectors by appropriately exploiting the Coulomb's electrostatic forces allowing thus the building of mats with a wider diversity of fibrous structures. [9][10][11] In this context, 1D aligned, [12] 2D, [9] and even 3D [13,14] microstructured nanofibrous mats can be obtained paving the way for various practical applications such as the elaboration of biomimetic scaffolds mimicking bone osteons, [15][16][17] increasing the alignment and porosity of the mats for better cell colonization in tissue engineering, [18] improving the efficiency and reepithelialization of wound healing, [19] inducing anisotropic mechanical properties enhancing the biomimicry [20] and even improving the light transmittance and pollutant filtration of membranes. [21][22][23] It has been shown that the charges carried by the suspended fibers hanging between the protuberances of patterned collectors play the most important role as they build an electrostatic template necessary for the controlled deposition of the electrospun fibers.…”
Section: Measurement and Modeling Of The Nanofiber Surface Potential During Electrospinning On A Patterned Collector: Toward Directed 3d mentioning
confidence: 99%
“…Clinically, the honeycomb structure is effective for bone formation because it makes it easier to supply blood and cells concerned with bone formation [ 29 ]. However, because the 0.2% offset load value of just the honeycomb structure was almost 700 N (data not shown), some tray morphology is considered necessary for strength.…”
Section: Discussionmentioning
confidence: 99%